2017
DOI: 10.1186/s40035-017-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and genotype-phenotype correlation analysis in patients with ATL1 mutations: A literature reanalysis

Abstract: BackgroundThe hereditary spastic paraplegias (HSPs) are a group of clinically and genetically heterogeneous disorders. Approximately 10% of the autosomal dominant (AD) HSPs (ADHSPs) have the spastic paraplegia 3A (SPG3A) genotype which is caused by ATL1 gene mutations. Currently there are more than 60 reported ATL1 gene mutations and the genotype-phenotype correlation remains unclear. The study aims to investigate the genotype-phenotype correlation in SPG3A patients.MethodsWe performed a reanalysis of the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…The current findings were consistent with the notion that mutations in SPAST , ATL1 , and REEP1 are the most common causes of autosomal dominant HSP. It has been reported that 10.56% of ATL mutation carriers show incomplete penetrance, and we believe modulator genes or other factors may influence the phenotype. The clinical features of patient with ATL1 c.1246C>T mutation is different with a previous report, in which the pedigree with this mutation had a late‐onset, mental impairment, and thin corpus callosum in brain MRI .…”
Section: The Clinical Features Of 18 Probands With Hsp In Our Cohortmentioning
confidence: 80%
“…The current findings were consistent with the notion that mutations in SPAST , ATL1 , and REEP1 are the most common causes of autosomal dominant HSP. It has been reported that 10.56% of ATL mutation carriers show incomplete penetrance, and we believe modulator genes or other factors may influence the phenotype. The clinical features of patient with ATL1 c.1246C>T mutation is different with a previous report, in which the pedigree with this mutation had a late‐onset, mental impairment, and thin corpus callosum in brain MRI .…”
Section: The Clinical Features Of 18 Probands With Hsp In Our Cohortmentioning
confidence: 80%
“…Mutations in Atlastin-1 have been identified as the cause of SPG3A, an autosomal dominant form of hereditary spastic paraplegia (HSP; Zhao et al, 2001;Zhao and Liu, 2017). The HSPs are a group of clinically heterogeneous neurological disorders classified into "pure" or "complicated" on the basis of the clinical features (Blackstone, 2018;Shribman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More than 60 different ATL1 gene mutations have been described, mostly missense mutations but also a limited number of small deletions, small insertions, splice site mutations, and whole exon deletions (Blackstone, 2018). Nevertheless, the genotype-phenotype correlation remains utterly unclear (Zhao and Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily produced in the brain and the spinal cord in the central nervous system. In neurons, this protein is located mainly in the endoplasmic reticulum and it is responsible for endoplasmic reticulum tubular network biogenesis; also, it is located at the tip of neurons in the axonal growth cone, it directs the growth and development of the axons which transmit nerve impulses [14][15][16][17][18]. Mutations in the ATL1 gene are more common with early-onset HSP patients.…”
Section: Introductionmentioning
confidence: 99%